Study Evaluasi Terhadap Hasil Pengembangan Program Studi S1 Pgmi Pada Masyarakat Islam Kepulauan Di Kota Ternate - Silawane, Nurjannah; Ikrimah, Ikrimah; Bareki, Firda; Safan, Mita; Tusyakiroh, Aqila (Peneliti.net, 2023)
IAIN Ternate is one of the leading State Islamic Universities in the city of Ternate, while the PGMI Undergraduate study program at IAIN Ternate was held in 2014. The presence of the PGMI Undergraduate Study Program promises great hopes for stakeholders and the archipelagic Islamic community in Ternate City. In the effort to develop the PGMI Undergraduate study program, seeing the challenges of the world of work or the level of existing needs, graduates of the PGMI Undergraduate Program are really needed. Therefore, in order to be able to analyze the level of need, it is necessary to obtain accurate information from all parties about the prospects for developing the PGMI undergraduate study program, especially in the island Islamic community in the city of Ternate. From the results of this research, it can be concluded that: The results of the development process of the PGMI Undergraduate study program at the Faculty of Tarbiyah and Teacher Training IAIN Ternate, include: The Undergraduate PGMI Study Program FTIK IAIN Ternate has used the KKNI curriculum which focuses on the needs of stakeholders in the Islamic archipelago community, program development The PGMI Undergraduate study was carried out by establishing a partnership relationship with both public and private madrasah Ibtidaiyah in the city of Ternate, this partnership relationship is in the form of education and teaching, research and service to partner MI, this has been established since the 2016/2017 academic year until now, the results of program development PGMI Undergraduate studies namely the existence of assisted madrasahs, which are located in island areas in the city of Ternate, the results of the development of the PGMI Undergraduate study program can be seen from the increase in the number of students from year to year, and the results of the development of the PGMI Undergraduate study program can be seen from the holding of guest lectures (visiting professor) from Germany in the form of international training and seminar activities.